The role of patents and secrecy for intellectual property protection: theory and evidence - Malte Mosel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2012)
Traditionally patents are seen as the gold standard for intellectual property protection. But, in line with empirical findings that secrecy is considered more important for appropriating returns, recent theories predict that firms keep their most important inventions secret. This article reconciles both opposing views in a unifying framework, accounting for the main aspects causing the discrepancy: imperfect protection, patenting costs, and simultaneous innovations. Theoretical results on the relation between patenting and innovation size are then confronted with survey data for small European firms. Using a binary size measure, we find strong support for the traditional view that firms patent their most important innovations, but a continuous size measure reveals an inverted-U relation between patenting and size, as predicted by the unifying framework.
Keywords: D22; D23; K11; L16; O34; 330; Filing fees; imitation; innovation; probabilistic patent rights; R&D; simultaneous innovation; trade secrets; Innovation; Immaterialgüterrechte; Patent; Geschäftsgeheimnis; KMU; Industrielle Forschung; Theorie; EU-Staaten